JUDICIAL CONSIDERATION OF CHILD CUSTODY TO FATHER UNDER ARTICLE 105 OF INDONESIAN COMPILATION OF LAWS - Fatonah, Fatonah; Amalia, Lia; Abas, Muhamad (Dusturiyah: Jurnal Hukum Islam, Perundang-undangan dan Pranata Sosial, 2024)
This research explores the regulation of child custody for minors under Indonesian law following divorce, based on Decision Number 3208/pdt.G/2020/PA.Krw. Divorce entails the allocation of custody to one of the separating partners, either the mother or the father. Additionally, parents are obliged to educate their children until they reach the age of 18 or marry. The study adopts a normative juridical method, finding that the regulation of child custody for minors is outlined in Article 105 of the Compilation of Islamic Law, granting a mother the right to raise a child who is not yet mature (mumayyiz) or under 12 years old, while a mature child is returned to them. However, in divorce cases, these rules may not apply, and judges have the discretion to consider the child's interests under Law Number 1, Article 41, with custody potentially revoked under Law Number 1 of 1975, Article 45(1). Custody of minors under Islamic Law is governed by Law Number 23 of 2002 concerning Child Protection, amended by Law Number 35 of 2014, Article 105, which assigns custody of children under 12 to their mothers, yet court rulings may favor fathers.